Application of stabilized hypobromite for controlling membrane fouling and N-nitrosodimethylamine formation. (February 2020) - Fujioka, Takahiro; Yoshikawa, Hiro; Eguchi, Masahiro; Boivin, Sandrine; Kodamatani, Hitoshi
Abstract: Chloramination is a conventional and successful pre-disinfection approach to control biological fouling for reverse osmosis (RO) treatment in water reuse. This study aimed to evaluate the possibility of using a new disinfectant—stabilized hypobromite—in controlling membrane fouling and the formation of a particular carcinogenic disinfection byproduct (DBP)— N -nitrosodimethylamine (NDMA). Our accelerated chemical exposure tests showed that the new disinfectant reduced the permeability of a polyamide RO membrane permeability from 6.7 to 4.1 L/m 2 hbar; however, its treatment impact was equivalent to that of chloramine. The disinfection efficacy of stabilized hypobromite was greater than that of chloramine when evaluated with intact bacterial counts, which suggests its potential for mitigating membrane biofouling. Additional pilot-scale tests using synthetic wastewater demonstrated that pre-disinfection with the use of stabilized hypobromite inhibits membrane fouling. Among 13 halogenated DBPs evaluated, the formation of bromoform by stabilized hypobromite was higher than that by chloramine at a high dose of 10 mg/L, thus suggesting the need for optimizing chemical doses for achieving sufficient biofouling mitigation. NDMA formation upon stabilized hypobromite treatment in two different types of actual treated wastewaters was found to be negligible and considerably lower than that by chloramine treatment. In addition, NDMA formation potential by stabilized hypobromite was 2–5 orders of magnitude lower than that by chloramine. Our findings suggest the potential of using stabilized hypobromite for controlling NDMA formation and biofouling, which are the keys to successful potable water reuse. Graphical abstract: Image 1 Highlights: Stabilized hypobromite showed more bactericidal effects than monochloramine. Pre-disinfection by stabilized hypobromite inhibited membrane fouling at pilot scale. NDMA formation by stabilized hypobromite in two treated wastewaters was negligible. NDMA FP by the new chemical was 2–5 orders of magnitude lower than chloramine.